Efektivitas Pengelolaan Keuangan Kecamatan berazaskan Akuntabilitas, Transparansi dan Kompetensi di Kabupaten Grobogan - Alvianita, Devi; Soegiastuti, Janti (Serat Acitya, 2025)
The problem faced by the level of public trust related to transparency, accountability and competence towards the sub-district government is still lacking and not yet optimal. This is because the sub-district government is not optimal in providing access and important information about agendas, programs and financial management so that the public does not fully believe that the government is transparent. and accountable. The population of this study was all employees at the District Office in Grobogan Regency totaling 38 employees who were sampled using a saturated sampling technique or census. The analytical tools used in this research are multiple linear regression analysis and t test. The results of this research are that accountability, transparency and competence have a positive and significant effect on the effectiveness of financial management at sub-district offices in Grobogan Regency.